Fragments of subjectivity : a narrative of the relationship between postmodern and feminist theories in an attempt to redefine subjectivity - Boezak, Sonja Louise (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1999.